ISU GENDER DI INDONESIA DALAM RESPON NAHDHATUL ULAMA - Akhiriyati Sundari (LPPM IAIN Parepare, 2017)
This paper will examine the Nahdhatul Ulama's response to gender issues in Indonesia. In general, Nahdhatul Ulama's response to gender in this case is represented by the discourse of women's acceptance in the NU body is relatively good. This is seen from some important decisions issued by PBNU. Empowerment and gender mainstreaming within the structural framework of the Nahdhatul Ulama organization are seen in significant decisions for gender equality, including decision making after the 1997 Munas decision, how NU accepts women as president